Nature, ecology and environment and environmental impact. legal implications - Remy Llerena, Gastón (2021)
The essential components of our Earth system are four: the solid earth, water, air and living organisms. The first three are usually included in the term geosphere, the system includes non-living components of the Earth system. The last component is generally known under the name biosphere, which is the way of life and support integrated in the peripheral envelope of the planet life. Between the two systems there is a close relationship: Life on earth depends on the existence and functioning of the geosphere and it would not have its current configuration without the existence of living beings. All these components of the Earth system is what is called today the environment is being seriously affected by human will. Today, the environment undergoes continuous alterations in the natural, physical or biological systems whose impacts are not and often can not be located but are affecting the whole of the earth. Habitat destruction of living things, the changes in the boundaries of ecosystems is a result of deforestation unpunished, the scandalous desertification, aridity of the soil and the unbridled consumption of fossil food which has meant the emission into the atmosphere methane and nitrous oxide, poisonous gases that contribute to greenhouse toiled currently ravaging our planet. All this is the clear product of human activity on the environment. So the laws on the subject require assessment or environmental impact study (EIA) prior to initiation of any human activity that inevitably affect the environment. It aims to preserve the environment by minimizing the negative impact of human activity, with the aim of achieving proper relationship between man and nature and always respect biodiversity.